ANALISIS MERGER BNI SYARIAH MENJADI BSI SEBAGAI UPAYA MEMPERKUAT EKOSISTEM EKONOMI SYARIAH - Jaya, Rizal Alfit; Rachmania, Rachmania; Apriani H, Siska; Rosyada, Amrina (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2023)
Abstract The purpose of this study was to determine and analyze the development of BNI Syariah Bank after merging with three state-owned Syariah banks which are expected to be able to strengthen the national Islamic economic ecosystem and can contribute as an International-Scale Bank. This research uses quantitative methods with descriptive analysis approach. This study seeks to describe development with growth techniques The findings of the study explain that in terms of benefits, the merger activity that is carried out causes more profits than losses. The benefits are in the form of increasing the sharia economic ecosystem in Indonesia, strong capital owned, and being able to compete nationally and even globally global. Keywords: Merger, Sharia Economic Ecosystem, BNI Syariah, BSI